Soluble vascular endothelial growth factor receptor‐1 as a novel marker of arteriovenous fistula stenosis in hemodialysis patients. Issue 2 (5th November 2020) - Eroglu, Eray; Kocyigit, Ismail; Kahriman, Guven; Karakukcu, Cigdem; Tuncay, Aydin; Zararsiz, Gozde Erturk; Eren, Davut; Kalay, Nihat; Sipahioglu, Murat Hayri; Oymak, Oktay; Tokgoz, Bulent
Abstract: Introduction: Arteriovenous fistula (AVF) stenosis is one of the most important clinical problems in hemodialysis patients. The histopathological findings of neointimal hyperplasia and impaired angiogenesis have been well established in stenotic AVFs. Soluble vascular endothelial growth factor receptor‐1 (sVEGFR‐1) has been implicated in pathological angiogenesis. Thus, we aimed to investigate the association between sVEGFR‐1 and AVF stenosis in hemodialysis patients. Methods: This prospective cohort study included 70 patients with end‐stage renal disease. Forty‐five patients were included in the final analysis, and the median follow‐up period was 36 months. Venous stenosis was detected by physical examination and documented by fistulography. Blood samples were analyzed a day before the fistula operation, and serum levels of sVEGFR‐1 were measured. Findings: The median sVEGFR‐1 level was higher in the stenosis group than in the nonstenosis group (17 pg/mL [89.5%] vs. 5 pg/mL [19.2%], respectively; P < 0.001]. According to body mass index (BMI) categories, obese patients (BMI > 30 kg/m 2 ) had the shortest stenosis‐free survival (20 months [9.35–30.65]). Multivariate Cox analysis showed that sVEGFR‐1, serum creatinine, and parathyroid hormone levels were associated with AVF stenosis risk. Kaplan‐Meier survival curves showed that patients with less than the median value of sVEGFR‐1 (<6093.07 pg/mL) had longer cumulative stenosis‐free survival than patients with sVEGFR‐1 levels above the median value ( P < 0.001). Discussion: Increased levels of sVEGFR‐1 and obesity were found to be associated with AVF stenosis in hemodialysis patients.